Preliminary Exploration of Cyanobacteria in Peat Waters, Palangka Raya, Central Kalimantan, Indonesia - Chaidir Adam (Journal of Peat Science and Innovation, 2022)
Cyanobacteria were formerly known as blue-green algae and are currently considered algae-like Gram-negative bacteria belonging to the bacterial kingdom. Lack of scientific information on the presence and distribution of cyanobacteria species in peat water habitats, particularly in Central Kalimantan, Indonesia, which has extensive peat waters. This study aims to conduct a preliminary exploration as an initial action for further research on the diversity and distribution of cyanobacteria species in peat water ecosystems. The results of the study reported that 5 species of cyanobacteria were found to be present in the peat water habitat in Palangka Raya, Central Kalimantan, Indonesia, belonging to the orders Chroococcales, Oscillatoriales, and Synechococcales. The cyanobacteria species found in this study include Microcystis sp., Chroococcus sp., Oscillatoria sp., Arthrospira sp., and Pseudanabaena sp. These findings indicate that further research needs to be carried out to explore, identify and isolate cyanobacteria from peat waters to obtain more detailed and clear data as a basis for optimizing the potential and benefits of cyanobacteria for sustainable life.